2011
DOI: 10.1111/j.1756-5391.2011.01126.x
|View full text |Cite
|
Sign up to set email alerts
|

Visualization studies on evidence‐based medicine domain knowledge (Series 1): Mapping of evidence‐based medicine research subjects

Abstract: Objective To use visualization methods to illustrate and compare major subjects, domains, and developments in evidence-based medicine (EBM) in recent years. Method We analyzed MeSH terms and keywords in EBM articles in the MED-LINE and CNKI databases, and developed subject charts, research field relationship charts, and strategy coordination charts using word co-occurrence, PFNET algorithms, and visualization methods. Result Rapid developments and growth are taking place in EBM in China and around the world. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This is evident in the difference in the relative strength of nursing in evidence‐based medicine between China and other countries (67.1 vs. 18,365.8; ref. ). It has been suggested that nursing studies in China are greatly lacking compared with other countries, both in terms of their breadth and depth.…”
Section: Discussionmentioning
confidence: 97%
“…This is evident in the difference in the relative strength of nursing in evidence‐based medicine between China and other countries (67.1 vs. 18,365.8; ref. ). It has been suggested that nursing studies in China are greatly lacking compared with other countries, both in terms of their breadth and depth.…”
Section: Discussionmentioning
confidence: 97%
“…In clinical practice, EBM has been introduced into evidence‐based TCM, evidenced‐based nursing, evidence‐based quality management, and other domains. Studies on evidence‐based nursing account for a large proportion, but most are less creative with shallow research depth compared with relevant studies abroad (Shen et al., ). Furthermore, evidence‐based management in China requires further exploitation and development as it is still in its early stages.…”
Section: Discussionmentioning
confidence: 99%
“…We used the 2015 Medical Subject Headings (MeSH ® ), from the U.S. National Library of Medicine, as already done in other mapping research (Shen et al. , Komenda et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…We used the 2015 Medical Subject Headings (MeSH Ò ), from the U.S. National Library of Medicine, as already done in other mapping research (Shen et al 2011, Komenda et al 2015 As the same MeSH terms are often found in several sub-branches, we drew up a simplified, tailored thesaurus to avoid redundancy in the mapping process (the one exception being for kidney diseases, where no distinction could be made between male and female disorders). We also considered the [Phenomena and Processes -G] branch, because it contained some possible relevant health conditions, such as pregnancy or menopause.…”
Section: Description Of Systemic Conditionsmentioning
confidence: 99%